Genetic dissection of quantitative trait loci for spikelets compactness in two Yanzhan1‐derived recombinant inbred line wheat populations. (12th October 2022) - Hu, Wenjing; Wu, Hongya; Lu, Chengbin; Zheng, Xu; Jia, Jizeng; Xu, Weigang
Abstract: Spikelets compactness (SC) plays an important role in the yield improvement and Fusarium head blight (FHB) resistance of wheat. In this study, 151 recombinant inbred lines (RIL) derived from a cross between Yangmai 4 (YM4) and Yanzhan 1 (YZ1) and 143 RIL derived from a cross between Yangmai 5 (YM5) and YZ1 were used to construct two wheat hexaploidy genetic linkage maps, evaluate SC across three years and identify quantitative trait loci (QTL) for SC. A total of seven QTL were identified in two populations and explained the phenotypic variation ranging from 6.27% to 22.49%. Four QTL were co‐located in two genomic regions on chromosomes 2D and 6B, namely, QSc‐2D and QSc‐6B, respectively. Comparison analysis showed that QSc‐6B is a novel QTL, whereas QSc‐2D was located in the interval of Rht8 . Significant additive effects of QSc‐2D and QSc‐6B on SC were observed in two RIL populations. Moreover, the positive alleles of these two QTL extremely significantly increased grain number per spike (GNS) but did not have a significantly negative effect on thousand‐grain weight (TGW), kernel length (KL) and kernel weight (KW). Whether in spray or point inoculation, QSc‐6B did not significantly influence FHB resistance in two populations. However, QSc‐2D significantly affected FHB resistance in spray inoculation in YM4/YZ1 population. A breeder‐friendly Kompetitive Allele‐Specific PCR (KASP) marker KASP_6B for QSc‐6B has been developed and verified in a set of 181 wheat cultivars/lines. Furthermore, we preliminary analysed the candidate genes within the physical interval of QSc‐6B by sequence similarity, spatial expression patterns and collinearity analysis. TraesCS6B03G1206900, TraesCS6B03G1214800 and TraesCS6B03G1218300 show specific expression in spikelet. These results provide valuable information for map‐based cloning of QSc‐6B and a useful tool for wheat breeding.